Analisis Pemahaman Mitigasi Bencana Tanah Longsir Untuk Kalangan Siswa Dan Siswi Di Smp Kecamatan Balikpapan Kota - Marini, Andi; Muhammad Fachri F L, Andi; Pratama, Abimanyu; Irawan, Helmi; Alam Putra L A R, Chikita Wisnu; Rahmad Al Muslim, Yazid; Rizqy U Q, Fahreza (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
This study aims to assess the level of understanding among middle school students in Balikpapan City about landslide disaster mitigation. Using a survey method with questionnaires, the research analyzes students' knowledge, attitudes, and actions regarding landslides. The results show that most students understand the basics of landslides but lack awareness of effective mitigation measures. Challenges include limited education on the topic and less interactive learning methods. This study recommends integrating disaster mitigation topics into school curricula and conducting simulation-based training to improve students' awareness and preparedness for landslide risks. Keywords: Landslide Mitigation, Middle School Students, Balikpapan City